Moral and managerial perspectives on cooperatives: Towards a Luhmannian reconciliation - Vladislav Valentinov; Constantine Iliopoulos (Systems Research and Behavioral Science, 2025)
The recent literature on cooperatives includes two distinct and partly conflicting strands. The moral strand emphasizes cooperatives as a sustainable alternative to shareholder capitalism, while the managerial one problematizes the maintenance organizational costs that must be incurred by these organizations. To reconcile the disparity between these strands, we develop a Luhmannian view of how cooperatives navigate the precarious relationship between the economic function system and the societal environment. On this basis, we show that the maintenance organizational costs plaguing many cooperatives are indicative of an imperfect business case for providing a sustainable alternative to shareholder capitalism. Consequently, we view these costs as a reflection of the heightened managerial challenges involved in pursuing elevated moral objectives.
Keywords: 300; business case; cooperatives; Luhmann's systems theory; moral case